Verringern Management-Entlohnungskosten die Agency-Kosten? Empirische Evidenz von netzwerkorientierten und marktorientierten Unternehmenskontrollsystemen - Rafel Crespi-Cladera; Carles Gispert; Luc Renneboog (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
In the UK, the top executive remuneration policy is not geared towards the creation of value but compensation revisions are rather driven by changes in corporate size, measured by sales growth. This suggests that managing larger firms requires special managerial skills. Even in UK companies with high concentration of control, no significant pay-for-performance relation has been discovered. In Spain, CEOs of larger firms receive higher cash-based compensation than those of small companies. For Spanish listed firms, we find that increases in corporate value are followed by increases in implicit (cash-based) CEO remuneration. However, this positive pay-for-share price performance elasticity is not present in all Spanish corporations: a remuneration policy aiming at the maximisation of corporate value is present in companies with a high degree of shareholder control. Only strong blockholders seem to be able to impose their share price related compensation scheme upon management. It should be noted that share prices trigger increases in CEO remuneration only if the share price returns are higher than those of the industry peers. In Spanish firms without high control concentration, modifications in managerial remuneration depend upon changes in accounting returns in prior years: if the change in the firm's return on assets (ROA) outperforms the industry ROA, the executive directors' cash compensation increases in the subsequent period. In these companies, the lack of blockholders gives management more
Keywords: 330; Führungskräfte; Lohn; Vergütungssystem; Leistungsentgelt; Corporate Governance; Großbritannien; Spanien